Infestation of Broad Bean (Vicia faba) by the Green Stink Bug (Nezara viridula) Decreases Shoot Abscisic Acid Contents under Well-Watered and Drought Conditions - Ederli, Luisa; Brunetti, Cecilia; Centritto, Mauro; Colazza, Stefano; Frati, Francesca; Loreto, Francesco; Marino, Giovanni; Salerno, Gianandrea; Pasqualini, Stefania (Frontiers in Plant Science, 2017)
The response of broad bean (Vicia faba) plants to water stress alone and in combination with green stink bug (Nezara viridula) infestation was investigated through measurement of: (1) leaf gas exchange; (2) plant hormone titres of abscisic acid (ABA) and its metabolites, and of salicylic acid (SA); and (3) hydrogen peroxide (H2O2) content. Furthermore, we evaluated the effects of experimentally water-stressed broad-bean plants on N. viridula performance in terms of adult host-plant preference, and nymph growth and survival. Water stress significantly reduced both photosynthesis (A) and stomatal conductance (gs), while infestation by the green stink bug had no effects on photosynthesis but significantly altered partitioning of ABA between roots and shoots. Leaf ABA was decreased and root ABA increased as a result of herbivore attack, under both well-watered and water-deprived conditions. Water stress significantly impacted on SA content in leaves, but not on H2O2. However, infestation of N. viridula greatly increased both SA and H2O2 contents in leaves and roots, which suggests that endogenous SA and H2O2 have roles in plant responses to herbivore infestation. No significant differences were seen for green stink bug choice between well-watered and water-stressed plants. However, for green stink bug nymphs, plant water stress promoted significantly lower weight increases and significantly higher mortality, which indicates that highly water-stressed host plants are less suitable for N. viridula infestation. In conclusion two important findings emerged: (i) association of water stress with herbivore infestation largely changes plant response in terms of phytohormone contents; but (ii) water stress does not affect the preference of the infesting insects, although their performance was impaired.